Catalytic Decomposition of N2O over Co–Ti Oxide Catalysts: Interaction between Co and Ti Oxide. Issue 12 (20th May 2016) - Zhang, Chi; Zhang, Zhiping; Sui, Chao; Yuan, Fulong; Niu, Xiaoyu; Zhu, Yujun
Abstract: A series of Co x Ti catalysts with different Co/Ti molar ratios ( x= 0.2, 0.4, 0.6, and 0.8) were prepared by the sol‐gel method and used for N2 O decomposition. The catalysts were characterized by XRD, X‐ray photoelectron spectroscopy (XPS), TEM, temperature‐programmed reduction with H2, temperature‐programmed desorption of O2, diffuse reflectance UV/Vis, Raman spectra, and N2 adsorption–desorption measurements. The results indicate that the Co x Ti catalysts possess high Brunauer–Emmett–Teller (BET) surface area, more surface Co 3+, and even better structural stability than Co3 O4 as a result of the strong interactions between Co and Ti oxide. Deactivation occurred over time for the Co3 O4 catalyst, however, Co0.6 Ti maintains nearly 100 % N2 O conversion for at least 30 h. Moreover, the Co0.6 Ti catalyst showed much stronger resistance against 1.5 vol. % O2, 2.4 vol. % H2 O, or 1.6 vol. % NO in the feed compared with the Co3 O4 catalyst. The excellent activity of the Co0.6 Ti catalyst can be attributed to the higher amount of surface Co 3+ derived from the interaction of the Co and Ti oxide in the Co x Ti catalysts. Abstract : Nitrous oxide decomposition : A Co–Ti oxide catalyst with a Co/Ti molar ratio of 0.6 shows high catalytic stability and strong resistance against O2, H2 O, and NO for N2 O decomposition, which is attributed to the high amount of surface Co 3+ based on the interaction between the Co and Ti oxide.